The Effectiveness of Schema Therapy on Emotional Inhibition and Response to Stress in Young Girls with Symptoms of Generalized Anxiety Disorder - Hossein HabibiManesh; Negin Abjadian; Fatemeh Zeinali; Azadeh Tork; Mahin Gharaei (Iranian Journal of Educational Research)
Objective: The objective of the study was to examine the efficacy of schema therapy in addressing emotional inhibition and response to stress among young individuals diagnosed with generalized anxiety disorder. Methods: This research employed a semi-experimental design with a pre-test-post-test structure, including a control group. The statistical population for this study consisted of all young girls seeking assistance at the Afaq counseling center in 2022 due to psychological issues. Participants were randomly divided into two groups, with each group containing 15 individuals (15 in the control group and 15 in the experimental group). Data collection was conducted using the Affective Control Scale (Williams et al., 1997) and the Stress Response Inventory developed by Koh et al. (2001). Results: The findings of the research demonstrated that schema-based therapy has a positive impact on emotional inhibition and response to stress in young girls with GAD (P < 0.05). Conclusions: The results generally indicate that schema therapy has the capacity to assist individuals in producing more suitable reactions to stressful situations and managing their emotional state through the modification of their cognitive processes and interpretation of events.